Socioeconomic Determinants of Access to Primary Healthcare in Rural Population of Sindh, Pakistan: Primary Healthcare Access in Rural Sindh: A Socioeconomic Analysis - Haider, Shagufta; Shabbir, Safia; Tariq, Muhammad; Nayeem, Athar; Shafique, Hira; Sahitia, Sandeep (Pakistan Journal of Health Sciences, 2025)
Pakistan’s rural population lacks access to primary healthcare facilities due to various socioeconomic factors. Investigating these factors is essential to improve healthcare delivery to these people. Objective: The Current study explores the socioeconomic determinants that influence the access to primary healthcare services in rural Sindh, Pakistan. Methods: This cross-sectional study was conducted in five districts of Sindh: Hyderabad, Thatta, Badin, Tharparkar, and Larkana. A total of 300 participants were surveyed using a structured questionnaire. Demographic data along with education, occupation, Monthly Income, Access to Utilities, Distance to medical facility, Medical services Costs, Waiting Times, Doctor, medicine, and diagnostic facilities. Descriptive statistics and logistic regression were used to analyze the data. Results: The study found that 46.8% of respondents had no formal education, and 54.5% reported a monthly household income of less than 20,000 PKR. Barriers to healthcare included long distances to healthcare facilities (72%), lack of transportation (60%), high treatment costs (55%), and long waiting times (50%). Logistic regression revealed that education level, income, and proximity to healthcare services were significant determinants of access to healthcare. Conclusions: Socioeconomic factors such as education, income, and geographical distance significantly affect access to primary healthcare in rural Sindh. Targeted interventions, including improving healthcare infrastructure and addressing transportation and affordability issues, are crucial to enhancing healthcare accessibility in these areas.